Growth in The Presence of Organic Solvents in Pseudomonas Aeruginosa and Its Vitreoscilla Hemoglobin (Vhb) Recombinant Strain (Pajc) - Kahraman, Hüseyin; Geckıl, H. (Fırat University, 2016)
This study is concerned with the potential use of Pseudomomas aeruginosa and its recombinant strain carrying Vitreoscilla hemoglobin gene (vhb) for degradation of important harmful aromatic compounds as toluene, xylene, benzene and 1-Cl -2,4-Dinitrobenzene (CDNB). P. aeruginasa and recombinant strain were grown in 10 ml LB overnight at 37°C in a shaking water-bath at 200 rpm. High aeration/high agitation cultures were incubated in a gyrator water-bath at 200 rpm in flasks containing 20 ml medium. P. aeruginosa and its various strains are known for their ease of use characteristics allowing gene transfer, expression and capabilities of degrading the heterocyclic aromatic compounds which are mostly harmful to all organisms. In this study, degradation of these single ring aromatic compounds by the recombinant strain that bears the vhb and its parental wild-type strain P. aeruginosa was carried out.

Pseudomomas aeruginosa ile onun Vitreoscilla hemoglobin geni (vhb) klonlanmış rekombinant suşunun önemli endüstriyel aromatik kirleticilerden olan toluen, 1-Cl -2,4- Dinitrobenzen (CDNB), ksilen ve benzen yıkımı çalışılmıştır. P. aeruginosa ve rekombinat suşu, 200 rpm 37° C’de 10 ml LB ortamında gece boyu üretildi. Yüksek havalandırma koşulları için 200 rpm ve 20 ml erlende büyütüldüler. P. aeruginosa ve çeşitli suşları gen transferi, ekspresyonu gibi çalışmalarda oldukça yaygın olarak kullanılan ve canlılar için çoğu zaman zararlı ve canlılar tarafından yapılmayan birçok heterohalkasal bileşikleri doğal olarak yıkma kabiliyeti ve yüksek solvent direnci ile bilinmektedir. Bu çalışmada Vitreoscilla sp.’den elde edilen vhb kopyalanmış rekombinant suş ve onun konakçısı yabanıl tip P. aeruginosa’nın solvent yıkma kapasiteleri incelenmiştir.
Pseudomonas Aeruginosa ve Vitreoscilla Hemoglobini (Vhb) Taşıyan Rekombinant Suşunun (Pajc) Organik Solventlerin Varlığında Büyümesi